Facilitating Reading Comprehension by Making Use of Guessing From Context Strategy to Tackle Unfamiliar Words - LARABA, Samir (Journal of Human Sciences, 2011)
The present paper is an endeavor to gain an understanding of the students’ employed strategies to cope with unfamiliar words while reading. It further investigates whether making use of guessing from context strategy to compensate for unknown words contributes in better comprehension achievement. Foreign language learners are often faced with reading comprehension problems. Even though they have stronger word identification ability, they exhibit relative weakness in vocabulary. When reading different academic materials, they encounter unfamiliar lexical items that block their comprehension. Since reading involves the skill of deducing meaning of unfamiliar words, what strategy learners can use to tackle/approach them so that reading comprehension can be facilitated?